Obesity: A New Adverse Effect of Antibiotics? - Del Fiol, Fernando S.; Balcão, Victor M.; Barberato-Fillho, Silvio; Lopes, Luciane C.; Bergamaschi, Cristiane C. (Frontiers in Pharmacology, 2018)
Abstract: Since the introduction of antibiotics, they have been used freely, with their prescription occurring almost always when they were not necessary. The other major form of contact between humans and antibiotics, now unintentionally, is with the large amount of these drugs in the environment and in our food. The relationship between antibiotic use and the development of obesity has become increasingly evident and apparent in humans, with some authors clearly establishing the relationship between the large-scale use of antibiotics in the past 70 years and the "epidemic" of obesity that has occurred in parallel, almost as an adverse epidemiological effect. In the research effort entertained herein, a correlation between the use and abuse of antibiotics and the onset of obesity was investigated.